Market Reactions To Share Repurchase Announcements In Malaysia - Isa, Mansor; Siew , Peng Lee (Asian Academy of Management (AAM), 2014)
This paper examines share price behaviour surrounding share repurchase announcements in the context of information asymmetry and signalling hypothesis. We use event-type analysis to examine abnormal returns around three related repurchase announcements: announcement of the board’s decision, announcement of shareholder approval and announcement of actual share purchase. The results show that stock prices increase significantly in response to each of the three repurchase announcements, but there is no significant difference in the market reaction to firms that eventually make a repurchase versus firms that do not. We conclude that our results are consistent with the underpricing signalling hypothesis. Our results also show that small firms earn greater abnormal returns than large firms during each of the announcements, lending support to the information asymmetry hypothesis. Our multivariate regressions indicate that firm characteristics such as firm size, return on assets and the market-to-book ratio are found to be significantly related to the announcement-related abnormal returns. Finally, logit and probit results indicate that firms’ repurchase decision depends on firm size, profitability and price changes during announcements.